A transmission-type triple grating spectrograph for improved laser scattering diagnostics of low-density plasmas used in chemical analysis. Issue 9 (10th June 2020) - Finch, Kevin; Hernandez, Aldo; She, Yue; Shi, Songyue; Gamez, Gerardo
Abstract : An improved transmission-type triple grating spectrograph permits 2D mapping of plasma species via laser scattering closer to surfaces, at faster measurement time, and the lowest electron density detection limit reported. Abstract : A wide variety of plasma geometries and modalities have been utilized for chemical analysis to date, however, there is much left to be understood in terms of the underlying mechanisms. Plasma diagnostics have been used for many years to elucidate these mechanisms, with one of the most powerful techniques being laser scattering approaches. Laser scattering provides information about the energetic species distributions, in terms of kinetic energy and densities, which can provide invaluable insights into the fundamental processes of chemical analysis plasmas with minimal perturbation. Thomson scattering (TS) from free electrons is the most difficult to implement due to the extremely stringent instrumental requirements for discerning the signal from competing scatterers in low-density plasmas, such as those seen in analytical chemistry applications. Nonetheless, relatively few instruments have been developed to satisfy these stringent requirements. In this paper, the design and characterization of a transmission-type triple grating spectrograph (TGS), with high numerical aperture (0.25)/contrast (≤10 −6 at 532 ± 0.5 nm)/stray light rejection (∼1.8 × 10 −8 at 532 ± 22–32 nm) required for TS, will be presented. In addition, proof-of-principle measurements on glow discharges operated under typical optical emission spectroscopy (OES) conditions demonstrate the high light throughput and low limits-of-detection (∼10 9 cm −3 at ∼1 eV T e ) afforded by the new instrument.